38 One-year outcome of multi-vessel pci versus staged pci in st elevated myocardial infarction. (5th October 2017) - Prakash, B Srinivas; Sullivan, V; Gibson, B; Cosgrave, J; Crean, P; Maree, A; Murphy, R
Abstract : Background: In patients with multivessel coronary artery disease presenting with STEMI, the CVLPRIT and PRAMI trials recommend undertaking only culprit artery PCI at the time of Primary PCI (PPCI); staged revascularization may then be performed at a later stage, in the days to weeks after PPCI. Purpose: The aim of this study was to review patients presenting with STEMI and multivessel disease and compare one-year outcomes of those undergoing multivessel PCI (MVPCI) at the time of PPCI to those undergoing staged PCI after initial acute culprit artery intervention. Methods: St. James's Hospital is Dublin's largest PCI centre. We identified all patients undergoing PPCI for STEMI between January and December 2015 using the Code STEMI database. Electronic health records, chart review and HIPE data were used to further characterize patients. The number of patients undergoing MVPCI during index procedure was recorded, as was the number undergoing staged intervention. Those referred for CABG were excluded from further analysis Average patient length of stay and need for re-intervention and mortality at one year were noted. Results: There were 417 patients with a confirmed diagnosis of STEMI, either clinically or angiographically; out of this 364 (87.2%) underwent PPCI. 153 patients (36.6%) presenting with STEMI had multi-vessel coronary artery disease, 136 (88.8%) had PCI and 17 (11.2%) had CABG. Of the 136 undergoing PCI for multi-vessel disease, 59 (43.4%) underwent MVPCI during PPCI; the average age of this group was 61 years and 12 (21%) were female. 77 (56.6%) patients underwent staged PCI, the average age was 62 years and 13 (17%) were female. Of those undergoing staged PCI 21 (27%) occurred during the index patient admission and 56 (73%) occurred as an outpatient. Within one-year of follow-up 4 (6.7%) in the MVPCI group and 6 (7.8%) in the staged PCI group had represented with recurrent MI requiring further revascularization, thus the relative risk of MVPCI patients presenting with recurrent MI was 0.8701, though the p value was non-significant at 0.82. 4 patients (6.7%) in MVPCI and 10 patients (12.9%) in staged PCI represented with angina, this represents a relative risk of 0.522, again with a non-significant p-value of 0.25. 1 patient died in MVPCI group, though this was due to non-cardiac causes; there were no deaths in the staged PCI group. Median hospital stay was 8.4 days (range 4.4–17.7) in the MVPCI group and 6.3 days (range 3.3–26.2) in the staged intervention group. Conclusion: In the largest Irish Primary PCI center, we found there no significant difference in patients representing with recurrent MI requiring repeat revascularization in multivessel PCI as compared to staged PCI. There was a trend for those undergoing staged PCI to represent with more angina than those undergoing MVPCI, though this did not reach statistical significance. There was no difference in length of stay between cohorts.